Software system architecture for control of tethered kites - Jochen Maaß and Michael Erhard (Springer, 2013)
In order to exploit high altitude wind energy, automatic computer control of tethered kites is a key to success. In this contribution, we report on the automation experiences and development issues on the software architecture gained by the development and operation of our ship propulsion kites during the last eight years. The first part puts focus on the requirements, the architecture and the signal flows of the distributed computer control system. The second part presents control system components in detail, introduces the respective challenges and explains how these are tackled by means of software engineering techniques. We conclude with a brief description on our hardware-in-the-loop simulation and test setup. © Springer-Verlag Berlin Heidelberg 2013.
Keywords: Software Architecture; Programmable Logic Controller; Controller Board; Flight Computer; Embed Controller